Relationship between board gender diversity and firm performance: Evidence from Malaysian firms / Mohd Fairuz Adnan, Nurshamimi Sabli and Azizah Abdullah - Adnan, Mohd Fairuz; Sabli, Nurshamimi; Abdullah, Azizah (Universiti Teknologi MARA Cawangan Pahang, 2013)
The purpose of this study is to investigate the association between board diversity and firm performance of 26 government-linked companies (GLCs) and 26 non-government-linked companies (non-GLCs) in Malaysia. The study focuses on gender variable to explain the board diversity and tests its relationship towards firm performance as measured by return on equity (ROE) and return on asset (ROA). A final sample of 196 GLCs and non-GLCs listed on the Bursa Malaysia are used across four years from 2007 to 2010. The results fail to satisfy the expectation made for this study, thus rejecting the hypothesis that gender board diversity is positively related to firm performance. In conclusion, this study could not establish that gender diversity on boards would enhance firm performance due to the small average samples of women directors on the board of Malaysian companies.